Enhancing Sales Turnover: Leveraging Product Quality and Pricing with Customer Satisfaction as the Mediator - Herniyati; Muslikh (SAN Scientific, 2024)
The purpose of this study is to find out how product quality and pricing affect sales turnover through customer satisfaction and find out whether product quality and pricing affect sales turnover through customer satisfaction in the Islamic view. This type of research used in this study is a associative study, the sample in this study were consumers of perpetual Arya Jaya LPG gas agents, totaling 50 people, while the sampling technique using the saturated Non Probability Sampling that is Sampling method census. Data analysis techniques used are path analysis, and multiple tests. The results showed that these results indicate product quality and pricing have a positive and significant effect on customer satisfaction, but the influence of product quality has positive and not significant results on sales turnover, and pricing on sales turnover has a positive and significant effect. Managerial implications of leveraging product quality and pricing to enhance sales turnover, with customer satisfaction as the mediator. Understanding the interplay between these factors is crucial for managers seeking to optimize their marketing strategies and drive business growth. By focusing on enhancing product quality and implementing competitive pricing strategies, managers can effectively influence customer satisfaction.